Contours and Constraints of an Autism Genetic Database. Scientific, Social and Digital Species of Biovalue - Singh, Jennifer S. (Tecnoscienza – Italian Journal of Science & Technology Studies, 2018)
This paper examines the scientific, social and digital processes that shape multiple forms of biovalue evident in the development, participation and use of the Simons Simplex Collection (SSC), the largest autism genetic databases in North America. Based on interviews with SSC study participants and investigators, as well as a content analysis of a range of SSC materials, this empirical study makes visible the various contours of biovalue that are entangled between scientists who use this data for autism research, families who donate their blood and medical information to gain access to needed resources, and digital networks of exchange that make hybrid connections between and among these emergent biosocial communities. By examining the production of and interactions between scientific, social and digital forms of biovalue this paper highlights the constraints embedded within this heterogeneous assemblage to offer a critical account of the limits of the SSC and subsequent knowledge production. I contend that while the multi-dimensionality of biovalue built into the fabric of the SSC structure creates various contours of biovalue, it structurally constrains the types of production and knowledge flows that are allowed to be conceived and generated.